Good quality of life in former Buruli ulcer patients with small lesions: long-term follow-up of the BURULICO trial. - Sandor Klis; Adelita Ranchor; Richard O Phillips; Kabiru M Abass; Wilson Tuah; Susanne Loth; Kristien Velding; Tjip S van der Werf; Ymkje Stienstra (PLoS Neglected Tropical Diseases)
Background Buruli Ulcer is a tropical skin disease caused by Mycobacterium ulcerans, which, due to scarring and contractures can lead to stigma and functional limitations. However, recent advances in treatment, combined with increased public health efforts have the potential to significantly improve disease outcome. Objectives To study the Quality of Life (QoL) of former Buruli Ulcer patients who, in the context of a randomized controlled trial, reported early with small lesions (cross-sectional diameter <10 cm), and received a full course of antibiotic treatment. Methods 127 Participants of the BURULICO drug trial in Ghana were revisited. All former patients aged 16 or older completed the Dermatology Life Quality Index (DLQI) and the abbreviated World Health Organization Quality of Life scale (WHOQOL-BREF). The WHOQOL-BREF was also administered to 82 matched healthy controls. Those younger than 16 completed the Childrens' Dermatology Life Quality Index (CDLQI) only. Results The median (Inter Quartile Range) score on the DLQI was 0 (0-4), indicating good QoL. 85% of former patients indicated no effect, or only a small effect of the disease on their current life. Former patients also indicated good QoL on the physical and psychological domains of the WHOQOL-BREF, and scored significantly higher than healthy controls on these domains. There was a weak correlation between the DLQI and scar size (ρ = 0.32; p<0.001). Conclusions BU patients who report early with small lesions and receive 8 weeks of antimicrobial therapy have a good QoL at long-term follow-up. These findings contrast with the debilitating sequelae often reported in BU, and highlight the importance of early case detection.